Radiation Kilovoltmeter for X-Ray Diagnostic Equipment (Texas Journal of Engineering and Technology, 2023)
The paper considers the calibration of the X-ray machine 12L7UR, which shows that to perform the calibration, the minimum step of changing the additional filters and the step of the anode voltage are selected and a correspondence is established between the readings of the verified Piranha instrument and the measured values of the reduced scattering coefficient